Surfactant-mediated morphology and fluorescent properties of amino acids-based lanthanide coordination polymers1. Issue 84 (16th September 2015) - Tan, Hongliang; Li, Qian; Ma, Chanjiao; Lu, Zhang-Hui; Fu, Zheng; Xu, Fugang
<x xml:space="preserve">Abstract</x> The morphologies and fluorescent properties of Phe/Tb CPs can be mediated by surfactants with different characteristics.